Comparing chemical reaction networks: A categorical and algorithmic perspective - Cardelli, L; Tribastone, M; Tschaikowski, M; Vandin, A (Elsevier, 2017)
We study chemical reaction networks (CRNs) as a kernel model of concurrency provided with semantics based on ordinary differential equations. We investigate the problem of comparing two CRNs, i.e., to decide whether the solutions of a source and of a target CRN can be matched for an appropriate choice of initial conditions. Using a categorical framework, we extend and unify model-comparison approaches based on dynamical (semantic) and structural (syntactic) properties of CRNs. Then, we provide an algorithm to compare CRNs, running linearly in time with respect to the cardinality of all possible comparisons. Finally, using a prototype implementation, CAGE, we apply our results to biological models from the literature.